IMPROVEMENT OF OIL PRODUCTION BY MATRIX ACIDIZING OF A WELL IN SANDSTONE RESERVOIR - Darel Sontia Fouazong; Isidore Komofor Ngongiah; André Chéagé Chamgoué; Alain Francis Talla; Jean Jacques Dikongue Jemea (Romanian Journal of Petroleum & Gas Technology)
This paper focuses on investigating the reasons behind the low productivity of a confidentially named well, referred to as X102, in sandstone reservoirs. The objective is to enhance the well’s productivity through the implementation of acidizing techniques. The paper makes a significant contribution to the existing literature in this field by expanding the knowledge base and providing an economic analysis of acidizing oil wells. The assessment of the X102 well indicates that it exhibited initial productivity from the natural energy of the oil reservoir, demonstrating an oil flow rate of 307 barrels per day with a skin value of 35. After 3 years of production, the X102 well experienced a decline in productivity due to fines migration. Excel software was employed to process well completions, reservoirs, production, well tests, and economic data. The Horner plot slope was used to calculate the damage, Pipesim software extracted the initial profile of the X102 well, and StimCADE software facilitated the acidizing design. Following the implementation of acidizing, a reduction in fines flow was observed, resulting in a decrease in skin value from 35 to 5. The acid treatment successfully dissolved the fine particles, leading to an increased oil flow rate of 1006 barrels per day. Economically, acidizing proved suitable, generating a profit of $44,062,800 and achieving a return on investment in 89 days over a 2-year production period.